Globalização e desigualdade de renda no Brasil: dimensões, efeitos e assimetrias regionais - Lediany Freitas de Campos (2020)
In a context of growing international integration and trade revolution, coupled with a permanent concern with inequality, the distributional impact of globalization is being discussed, whether it contributes to an increase in inequality or if it benefits nations by making places and people less unequal. In this sense, this work aims to explore globalization in its multidimensional character, specifically its effects in Brazil, incorporating the discussion with data that contemplate aspects other than trade flows. In addition, it investigates the effects of globalization, and of trade opening, on income inequality in Brazil, in terms of income distribution and differential wages by quantiles and by level of qualification, punctuating regional asymmetries. From a theoretical point of view, this study compiled several approaches that deal with the possible effects of globalization on the factors of production and their prices, having as a starting point the Heckscher-Ohlin-Samuelson model of international trade. Combining commercial openness with technological changes, the Skill-Biased Technological Change theory covers differentials by qualification. The spatial distribution is treated by the New Economic Geography and, added to the others, the insights of institutionalist theory, human capital and agglomeration about the influences on wage differentials are addressed. In order to bring more precision to the discussion of the phenomenon of globalization in the Brazilian context, the second chapter presents a proposal for the elaboration of a Regional Globalization Index for Brazil (IRG-Brazil). It is an unprecedented index for Brazil, of a multidimensional character, which encompasses the economic, social, cultural and political dimensions, prepared with the support of the Principal Component Analysis, with data obtained from different sources, for the period from 2001 to 2014. Through the IRG, it can be seen that characteristics in addition to foreign trade, especially those with a social dimension, such as immigration and tourism, are relevant to measure the international integration of States, and that there are regional asymmetries to be addressed. The most globalized states are RJ, SP, RS and PR, while states in the Northeast and North regions such as AL, RO, PI and PB are the least globalized, however, all increased the globalization index in the period. In possession of the IRG, it was used as a proxy for globalization, and opposed to trade openness, in order to capture its effects on income inequality in terms of income and wage distribution. Based on data from the National Household Sample Survey, indicators with different measures were used: average income inequality (Gini and Theil coefficients), polarized income inequality (R8020 and R1040) and labor income inequality (P9010 and Rquali). Based on estimates for panel data and quantile regression, it can be inferred that, unlike trade openness, the effects of globalization, as measured by the IRG, are of an increase in income inequality, with different proportions between regions. The greatest effects are felt by the Northeast region. The impacts are greater in the indicators that capture the ends of incomes, that is, globalization further widens the income gap between the top and bottom of the distribution. On wages, the effects of globalization are positive, but they benefit more from higher wages, compared to lower wages, and the wages of the most qualified, relative to the least qualified, and in some cases their wages are reduced. When using proxy for trade opening, the results indicate that wages decrease only in the Northeast region. Thus, it can be seen that globalization contributes to accentuating the regional heterogeneity that already exists in Brazil and, although it presents economic gains, it generates social costs, since its benefits are not evenly distributed among regions and among individuals.